Political dramaturgies and theatre spectatorship : provocations for change - Tomlin, Liz (Methuen drama engage, 2019)
"Has political theatre lost its potency and ability to effect change? Are audiences less inclined to be moved and less able to imagine alternative political realities in our individualized age? What strategies should theatre makers employ to respond to our present climate in ways that are both affective and effective? In this important study Liz Tomlin argues that the capacities of the contemporary and future spectator to be 'effected' or 'affected' by politically-motivated theatre needs to be urgently re-evaluated in light of the current political and philosophical climate. Drawing on a wide range of philosophical, psychological and sociological research Tomlin proposes that politically-motivated practice needs to take into account the spectator's decreasing capacity for empathy and ability to imagine the future, and an understanding of how individualism has replaced collectivism as the seemingly rational human response to danger to the self. She offers a re-evaluation of politically-motivated models of contemporary theatre such as Brechtian ideology critique, radical tragedy, documentary, verbatim and relational theatre practices in order to rigorously interrogate if and how theatre can best contribute to the emerging resistance to global neoliberal capitalism. Work analyzed ranges from dramatic texts including George Brant's Grounded, David Greig's The Events and Caryl Churchill's Advice to Iraqi Women and Far Away to contemporary performance by Stan's Cafe, Ontroerend Goed, Coney and Kaleider; to new performance writing by Chris Thorpe and Andy Smith"--